2004
DOI: 10.1093/cercor/bhi007
|View full text |Cite
|
Sign up to set email alerts
|

Action Observation and Acquired Motor Skills: An fMRI Study with Expert Dancers

Abstract: When we observe someone performing an action, do our brains simulate making that action? Acquired motor skills offer a unique way to test this question, since people differ widely in the actions they have learned to perform. We used functional magnetic resonance imaging to study differences in brain activity between watching an action that one has learned to do and an action that one has not, in order to assess whether the brain processes of action observation are modulated by the expertise and motor repertoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

111
1,043
16
33

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,602 publications
(1,203 citation statements)
references
References 46 publications
111
1,043
16
33
Order By: Relevance
“…On the one hand, the behavioral results from Experiment 1 dovetail with recent fMRI (Costantini et al, 2005) and TMS findings that biomechanically possible and impossible actions are coded similarilysimilarly by mirror/common coding mechanisms; on the other, the results of Experiment 2 are consistent with recent behavioral (Casile & Giese, 2006), developmental Sommerville, Woodward, & Needham, 2005), and neuroimaging (Buccino et al, 2004;Calvo-Merino et al, 2005Costantini et al, 2005) studies relating the representation of perceived actions to the observer's own ability to perform the action. Calvo-Merino and colleagues (2006), for example, presented expert ballet dancers with examples of dance moves that either were in their own motor repertoire or were performed only by opposite-gender dancers, finding increased activation in mirror circuits for the samegender moves.…”
Section: Attentional Weighting Effects On Automatic Imitationsupporting
confidence: 81%
“…On the one hand, the behavioral results from Experiment 1 dovetail with recent fMRI (Costantini et al, 2005) and TMS findings that biomechanically possible and impossible actions are coded similarilysimilarly by mirror/common coding mechanisms; on the other, the results of Experiment 2 are consistent with recent behavioral (Casile & Giese, 2006), developmental Sommerville, Woodward, & Needham, 2005), and neuroimaging (Buccino et al, 2004;Calvo-Merino et al, 2005Costantini et al, 2005) studies relating the representation of perceived actions to the observer's own ability to perform the action. Calvo-Merino and colleagues (2006), for example, presented expert ballet dancers with examples of dance moves that either were in their own motor repertoire or were performed only by opposite-gender dancers, finding increased activation in mirror circuits for the samegender moves.…”
Section: Attentional Weighting Effects On Automatic Imitationsupporting
confidence: 81%
“…In the case of performing arts such as dance, the observer's aesthetic experience is presumably grounded in the responses of their neural sensory, motor and affective circuits to the expressive actions of the dancer's body. Consistent with this account, viewing dance recruited a network of parietal and premotor areas in a manner dependent on the viewer's previous sensorimotor experience (Calvo-Merino et al, 2005). Importantly, dance movements and dance postures may be judged beautiful or otherwise, quite independently of whether the dancer is judged to be personally attractive or not (Brown et al, 2005).…”
Section: Introductionmentioning
confidence: 71%
“…Recent studies in both humans and other animals have shown sensory (Keysers et al, 2004;Downing et al, 2001), motor (Di Pellegrino et al, 1992, Calvo-Merino et al, 2005 and affective responses (Wicker et al, 2003) in several cortical areas triggered by viewing conspecifics. These responses are often interpreted with reference to a hypothesis of 'the social brain ' (Frith and Frith, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The overlapping neuronal populations and cortical regions in human and non-human primates has been taken by some as a mechanism for observational learning, by means of implicit neural simulation of the observed action (Calvo-Merino et al, 2005;Jeannerod, 2001). However, the concept of mirror neurons, as typically discussed, offers no insight into how the sensorimotor system reacts to the observation of the commonplace errors that must drive motor learning.…”
Section: Introductionmentioning
confidence: 99%